A reshaping recovery: the reverse shoulder arthroplasty triumphs in salvaging chronic four-part proximal humerus fractures - Kee, Hoe Teong; Yeak, Raymond D.K.; Ahmad Hanif, Khairil Anwar; Seri Masran, Siti Munira; Che-Hamzah, Fahrudin (Springer, 2023)
The aging population is witnessing a steady increase in the incidence of displaced proximal humerus fractures, particularly among elderly patients. Such fractures pose a significant challenge to orthopedic surgeons, given the complex interplay of factors involved, including fracture displacement, comminution, compromised bone quality, and the presence of concurrent medical comorbidities. While open reduction internal fixation (ORIF) remains a viable treatment option for these fractures, it is a technically demanding procedure associated with a high incidence of complications. Recently, reverse total shoulder arthroplasty (RTSA) with tuberosity repair has gained popularity as a successful approach for addressing such fractures. The present case report details a unique and complex case of a chronic four-part proximal humerus fracture, complicated by avascular necrosis of the humeral head, fracture non-union, and hardware penetration. The patient was successfully treated through a reverse shoulder arthroplasty procedure, highlighting the effectiveness of this surgical approach in such challenging scenarios. The advantages of RTSA in this context include the potential to address avascular necrosis, non-union, and hardware complications, as seen in our patient. Additionally, the procedure can restore functional independence and improve the overall quality of life in these challenging cases.